The Analysis Of Coordinating Conjunction In The Adventures Of Huckleberry Finn Novel - Dewi, Ni Putu Jeni Aswaria (ID Solutions, 2024)
This research objective is to categorize and finding various types of coordinating conjunctions as well as their syntactic structures in Mark Twain’s novel The Adventures of Huckleberry Finn. The data source from this study was a novel by Mark Twain titled “The Adventures of Huckleberry Finn”. By reading the book several times, noting the coordinating conjunctions, and categorizing the data in the novel according to the various categorize, and this study used the qualitative method with the data and observation technique. To convey the results both formal and informal methods was used, the informal method provides descriptive explanation of the coordinating conjunction types, whereas the formal method used a tree diagram to visually represent and illustrate syntactic structures of sentences. This research using theory from Quirk et al., (1985)[8] which provides an in-depth explanation of syntax to describe types of coordinating conjunctions and using from Brown and Miller (1991) [1]theory to examine the compound sentences' syntactic structure related to tree diagrams. The theory focuses on the structural representation of sentences using tree diagrams to illustrate syntactic relationships. Using these theories can help us to understand the sentence structure more clearly.The result of this study shown that are five coordinating conjunctions identify in the novel The Adventures of Huckleberry Finn, consisting with conjunctions “For” with 4 instances (1.76%), “And” 154 instances (67.85%), “But” 51 instances (22.46%), “Or” 2 instances (0.88%), and “So” 16 instances (7.05%).